THE INSTITUTION OF LOGIC OF PRODUCTION OF KNOWLEDGE IN EXISTING PUBLIC UNIVERSITY FACULTY IN FICTION OF A PRIVATE: THE CONSTRUCTION OF GROUP OF STUDIES (Fiep Bulletin - online, 2014)
Presenting the constitution of a group of studies, may be attitude, but to see this possibility as a further training for graduates of the course of Physical Education in a private HEI, will have felt the relevance of the topic presented. We have option to form a study group aiming to expand the disciplinary matrix, studying a little of everything, because we believe is crucial to an understanding and making position. The 1st. Barrier was found the internal resistance of the community, credited the resistance to production in the collective imagination of Physical Education which denies the possibility of studying outside of the area of health and not fetch consistency of its object in studies of a qualitative nature. The 2nd. Barrier appears when managers refer the representation of the establishment of the group of studies as allocation of public university. To realize this, the travel direction on the group, linking it as a place of continuous formation. I noticed that during the meetings of a ritual case that led studies of the practice of initiating scientific, which focused on the leisure through the daily life of various social groups, and pointed to evidence that the theoretical basis studied provided to (re) significance of the role of professor within the institution. Then we need to listen to them, categorizing the speeches of the academic who are in the group since 2004. We affirm that the basic theoretical worked at the beginning of the studies established links where the production of scientific knowledge through the initiation contributed to the formation professor of Physical Education. Consider the scientific initiation as a fundamental stage in the process, another important factor was that we point out that there is possibility to develop practices for IES public, as part of a small private college, where the differences are respected and that acts of a compromise teachers and administrators.
Keywords: Group of studies; production of knowledge; Imaginary